Kebutuhan akan agama dari perspektif barat menurut Teori Conflict dari George M. Stratton - Suaedy, Maulana Hikam (Maliki Interdisciplinary Journal, 2024)
This article examines the conflict between the need for religion and secularism in the West from the perspective of George M Stratton’s conflict theory. Although many previous articles have on this topic, this article provides a more in-depth and different perspective on the conflict. The importance of this topic lies in the important role of religion in Western society and how the need for religious in Western society and how the need for religion can be accommodated in the development of secularism in the West. the development of secularism in the West. George M Stratton’s conflict theory views that conflict between the need for religion and the development of secularism in the West. The purpose of this article is to provide a more comprehensive understanding of the of the conflict between the need for religion and secularism in the West from the perspective of George M Stratton’s conflict theory. George M Stratton’s theory of conflict. This article also aims to reassess how religion plays an important role in Western society and to what extent the need for religion can be accommodated in the development of secularism. religion can be accommodated in the development of secularism in the West. Results and discussion this article concludes that the conflict between the need for religion and secularism in the Western society is still an ongoing debate within George M Stratton’s conflict theory. Religion still plays an important role in Western society, but to what extent can the need for religion be accommodated in Western society? the need for religion can be accommodated in the development of secularism in the West is a challenge. This article hopes to provide a more understanding of the conflict between the need for religion and secularism in the West from a perspective of George M Stratton’s conflict theory.